The Need of Computer Modelling and Simulation (CMS) Competency among Employers in Malaysia - Ismadi, Mohd Zulhilmi P.; Kurnia, Jundika C.; Sulaiman, Shaharin A.; Hassan, Suhaimi; Awang, Mokhtar; Yusoff, Puteri S.M.M.; Urquia, Alfonso (MATEC web of conferences, 2018)
With the continuous improvement in Computer Modelling and Simulation Environment (CMSE) applications being made, computer modelling and simulation (CMS) is proven a better alternative as opposed to conventional physical modelling. The advancement of computing hardware allows accurate results to be obtained faster, safer and at a fraction of its original cost. Despite the proven advantages, CMSE adoption among companies may be fairly new in Malaysia. This study is aimed at quantifying the demand of CMSE specialists in Malaysia as well as gaining insights in the companies’ requirements of specialists’ knowledge, competencies and skills. Thus, a survey, consisted of 3 main parts, was conducted among industries in Malaysia as a tool of measurement of the demand. The survey included questions related to the general information of the organization, specialists’ competencies relation to the job scope, and finally the professional and educational standards among specialists. In general, it was found that practically-competent specialists in CMSE are in high demand among engineering companies. Furthermore, professional courses through distance learning would be of high interest among companies to send their employees to gain practical competency in CMSE.